Non-24-Hour Sleep–Wake Rhythm Disorder in the Totally Blind: Diagnosis and Management - Quera Salva, Maria Antonia; Hartley, Sarah; Léger, Damien; Dauvilliers, Yves A. (Frontiers in Neurology, 2017)
Many aspects of human physiology and behaviour are dominated by 24-hour circadian rhythms that have a major impact on our health and well-being. These include the sleep-wake cycle, alertness and performance patterns, and many daily hormone profiles. The rhythms are spontaneously generated by an internal "pacemaker", the suprachiasmatic nuclei within the anterior hypothalamus. This master clock has, for most humans, an intrinsic rhythm slightly longer than 24 hours. Daily retinal light exposure is required to keep these circadian rhythms synchronized with the external 24-hour solar environment. This daily synchronization process generally poses no problems for sighted individuals although they experience some of the consequences of circadian desynchrony when "jetlagged" or working night shifts. However, many blind people with no perception of light experience periodical circadian desynchrony. This is due to the absence of light information to the hypothalamic circadian clock, resulting in poor synchronisationsynchronization of circadian rhythms. Affected patients experience cyclical or periodic episodes of poor sleep and daytime dysfunction, severely interfering with social, academic and professional life. The diagnosis of Non-24 Sleep-Wake Rhythm Disorder Syndrome, also named free-running disorder, non-entrained disorder or hypernycthemeral syndrome remains challenging from a clinical point of view due to the cyclical symptoms and should be confirmed by measurements of circadian biomarkers such as urinary melatonin to demonstrate a circadian period outside the normal range. Management includes behavioural modification and melatonin. Tasimelteon, a novel melatonin receptor 1 and 2 agonist, has demonstrated its effectiveness and safety with an evening dose of 20 mg in and is currently the only treatment approved by the FDA and the EMA.